Rights of Wetlands: a new relationship with wetlands in Sri Lanka - International Water Management Institute (International Water Management Institute, 2024)
IWMI, with partners from Kenya, the USA, the UK and Sri Lanka, is addressing wetland loss and degradation using a “rights of wetlands” approach, whereby wetlands are afforded the same consideration and protection as human beings